PERAN PEMERINTAH DAERAH DALAM MENGENTASKAN KEMISKINAN DI KABUPATEN TANGERANG PROVINSI BANTEN - Marthalina Marthalina (Institut Pemerintahan Dalam Negeri, 2018)
ABSTRACT Tangerang Regency has many potential natural resources and human resources that should be added value in increasing the economic potential of the community. However, the people’s life in Tangerang district is still living in poverty. Looking at the facts in the field that there are still many people living in slums, the researchers need to conduct a study on how the role of local government in Tangerang District eradicate poverty in the region. The research design refers to secondary data from 2011-2015. The research was conducted by qualitative method with descriptive inductive writing to obtain data. The scope of writing is about the role of Local Government of Tangerang Regency in Eradicating Poverty as well as factors that inhibit and support the role. The results of this sresearch illustrates that the role of Local Government of Tangerang Regency in alleviating poverty is quite a lot of realized in 25 excellent programs that are implemented consistently cross-sectoral and cross-SKPD which is expected to solve synergic regional problems and integrated but the community is still constrained some access related to clean water facilities, especially in some densely populated areas or slums in coastal areas. Keywords: role, local government, poverty